Variation of spatiotemporal parameters in school children carrying different backpack loads: a cross sectional study - Páez-Moguer, Joaquín; Montes-Alguacil, Jesús; García-Payá, Irene; Medina-Alcántara, Francisco Miguel; Evans, Angela Margaret; Gijón-Noguerón, Gabriel (Springer Nature, 2019)
The purpose of this study was to analyze spatiotemporal parameters of gait in children using varyingly loaded Backpacks(BP). This cross-sectional study examined 231 schoolchildren (118 boys, 113 girls) aged six to 12 years, carrying a traditional BP to manipulate loading (Crossing Backpack Children Arpenaz 7 Litres, Junior Red Quechua). Load was added to the BPs in increments of 5%, 10%, 15% and 20% of the child's body weight. Spatio-temporal parameters were measured with the OptoGait system. Significant differences were observed in single support (p < 0.001), and double support (p < 0.001). No statistically significant differences were observed in step length (p = 0.959) between the five loading conditions. Similarly, no statistically significant differences were found in the contact phase (p = 0.208), although significant changes were seen between baseline, 15% of body weight (p < 0.005), and 20% of body weight (p < 0.005). The effect sizes from the ANOVA in the single support was low (0.015), and double support was moderate (0.02). Increased weight in BPs reduced both children's balance and single support, increased double support, but did not change step length. The children increase double support with heavier loads to help their balance. The spatio-temporal changes were most evident with BP loads between 15-20% of body weight. Affective responses, including the perception of heaviness or difficulty in carrying the schoolbags need to be included in further and prospective investigations.
Keywords: Spatiotemporal parameters; varyingly loaded Backpacks; gait